MCPIP1 expression positively correlates with melanoma‐specific survival of patients, and its overexpression affects vital intracellular pathways of human melanoma cells. Issue 4 (5th February 2021) - Nowak, Iwona; Brożyna, Anna A.; Zabłocka, Marzena; Student, Sebastian; Durbas, Małgorzata; Bugara, Beata; Rokita, Hanna
Abstract: The suppressive activity of monocyte chemoattractant protein 1‐induced protein 1 (MCPIP1) an inflammation‐related ribonuclease, has been described in a few cancer types but has yet to be assessed in the most common subtype of skin cancer: melanoma. Here, we have evaluated the MCPIP1 expression in melanoma tissues by reanalysis of publicly available transcriptome data from 89 melanoma samples, and immunohistochemical staining of 21 primary and 81 metastatic melanomas. Our data implicated decreased MCPIP1 expression in melanoma tumors compared to normal tissues, and positive correlation between high ribonuclease expression and melanoma‐specific survival of patients. To investigate the ribonuclease activity in melanoma cells, MCPIP1 was ectopically expressed in the MV3 human melanoma cell line. Following the transcriptome, proteome, and intracellular signaling of MCPIP1‐overexpressing MV3 cells was assessed via real‐time quantitative polymerase chain reaction, Western blot analysis, and RNAseq. MV3 cells overexpressing MCPIP1 exhibited a broad range of alterations in the transcriptome and proteome, as well as in the phosphorylation status of a number of proteins, strongly indicating MCPIP1‐dependent cell cycle arrest and inhibition of Akt/mTOR signaling in these cells. Moreover, we have shown, that MCPIP1 overexpression downregulates miRNA‐193a‐3p expression in MV3 cells. Furthermore, the majority of the described effects were dependent on the ribonucleolytic activity of the protein. The presented body of data strongly suggests a potential tumor suppressor role and possible future application as a positive prognostic marker of MCPIP1 protein in melanoma.